2004
DOI: 10.1038/sj.jhh.1001782
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial on sodium reduction in two developing countries

Abstract: Hypertension remains the most common cardiovascular risk factor in developing countries, yet the majority of patients have no access to pharmacological therapy. Population-wide preventive strategies, such as salt restriction, are an attractive alternative, but experience in resource-poor settings is limited. To address this question, we conducted a randomized crossover study of salt restriction in adults living in Nigeria and Jamaica in order to estimate the mean blood pressure (BP) response. After a 4-week ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 14 publications
0
48
0
Order By: Relevance
“…This is due to the fact that family members may share similar life style and genetic factors. It has been demonstrated that people who reported ever use of top added salt on plate had a positive association with hypertension which was evidenced elsewhere [20],[21]. It is already an established fact that a high salt diet disrupts the natural sodium balance in cells.…”
Section: Discussionmentioning
confidence: 92%
“…This is due to the fact that family members may share similar life style and genetic factors. It has been demonstrated that people who reported ever use of top added salt on plate had a positive association with hypertension which was evidenced elsewhere [20],[21]. It is already an established fact that a high salt diet disrupts the natural sodium balance in cells.…”
Section: Discussionmentioning
confidence: 92%
“…Individuals of African ancestry in the USA are at higher risk of developing hypertension [22][23][24][25] than those of European origin and there is evidence that they are more susceptible to sodium overload [26,27]. The possibility that a similar susceptibility occurs in the case of alcohol consumption should be confirmed in experimental models.…”
Section: Discussionmentioning
confidence: 96%
“…14, 2629 Our previous comparative trial in Nigeria and Jamaica demonstrated quantitatively similar responses to sodium reduction in normotensive individuals. 30 …”
Section: Discussionmentioning
confidence: 99%